To the question of information support of the systems of market of pedagogical work - D L Agranat (RUDN Journal of Informatization in Education, 2014)
2-y Selskohozaystvenniy str., 4, Moscow, Russia, 129226 In article actual aspects of functioning of information support in the field of the recruiting sphere are considered. Information opportunities of recruiting Internet resources for the market of pedagogical work are analyzed.